Cutting teeth [large type] - Baker, Chandler (Thorndike Press large print top shelf., 2023)
"Darby, Mary Beth, and Rhea are on personal quests to reclaim aspects of their identities subsumed by motherhood--their careers, their sex lives, their bodies. Their children, though, disrupt their plans when an unsettling medical condition begins to go around the Little Academy preschool: the kids are craving blood. Then a young teacher is found dead, and the only potential witnesses are ten adorable four-year-olds. Soon it becomes clear that the children are not just witnesses, but also suspects... and so are their mothers. As the police begin to look more closely, the children's ability to bleed their parents dry becomes deadly serious"--